In vitro antioxidant, anticancer activity acetone and methanol extracts of Carica Papaya - Dr. P. SAGADEVAN; JAYARAMJAYARAJ. K (International Journal of Pharma and Bio Sciences, 2018)
This study was done to examine antioxidant and cytotoxicity potential in the extracts of leaf from the traditionally used medicinal plant, Carica papaya. Antioxidant and cytotoxicity potential of crude methanol and acetone extract of Carica papaya were compared Hydroxyl radical scavenging activity Nitric oxide scavenging assay: The present study reveals the medicinal properties of the C. papaya the phytochemicals screening revealed the presence of various compounds such as acetone leaf extract of C. papaya shows the presence of alkaloids, saponins, flavanoids, terpenoids, glycosides, phenolic compounds. The methanol leaf extract shows the presence of alkaloids, saponins, flavanoids, terpenoids, glycosides, phenolic compounds, tannins and steroids. This confirmed the presence compounds which are responsible for good anti-microbial, anticancer and anti-oxidant properties of the study species. The antioxidant activity also notably significant and anticancer study revealed the importance of the study plant potential anticancer agent. The present study confirms the potentiality of the plant rich source of therapeutic value. Extensive study will provide a good source of medicinally important drugs in future.